Platforms, Promotion, and Product Discovery: Evidence from Spotify Playlists - Luis Aguiar; Joel Waldfogel (European Commission, Joint Research Centre (JRC), 2018)
Digitization has vastly increased the amount of new music produced and, because of streaming, has raised the number of songs available directly to consumers. While enhanced availability has levelled the playing eld between already-prominent and new artists, creators may now be highly dependent on platform decisions about which songs and artist to promote. With Spotify emerging as dominant major interactive music streaming platform, this paper explores the e ect of Spotify's playlists inclusion decisions on both the promotion of songs and the discovery of music by new artists. We employ four empirical strategies for measuring the impact of playlists on song success. First, we examine songs' streaming volumes before and after their addition to, and removal from, major global playlists. Second, we compare streaming volumes for songs just on, and just o , algorithmic top 50 playlists. Third, we make use of cross-country di erences in inclusion on New Music Friday lists, using song xed e ects, to explain di erences in streaming. Fourth, we develop an instrumental variables approach to explaining cross-country New Music Friday rank di erentials based on home bias. We find large and signi cant e ects: being added to Today's Top Hits, a list with 18.5 million followers during the sample period, raises streams by almost 20 million and is worth between 116,000 and 163,000. Inclusion on New Music Friday lists substantially raises the probability of song success, including for new artists.
Keywords: K42; L82; O34; O38; 330; Music Streaming; Music Industry; Copyright